1988
DOI: 10.1093/ajcn/47.3.433
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin precursor influenced by type of carbohydrate meal in healthy adults

Abstract: We compared the effects on the ratio of plasma tryptophan to large neutral amino acids (trp:LNAA) of two different carbohydrate meals (sucrose or starch, 120 g) and a contrasting meal of fat + protein given at breakfast to 10 healthy adults. Plasma glucose and insulin were also measured. The trp:LNAA ratio rose after both carbohydrate meals (p less than 0.001). Glucose and insulin peaks were higher after sucrose than starch, and trp:LNAA rose correspondingly higher (sucrose +34% and starch +20%, p less than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 22 publications
2
38
0
2
Order By: Relevance
“…In support of this, a correlation between plasma glucose and insulin, and peak Trp:LCNAA has been reported (36). Therefore, an HC diet, especially one with a high GI, would promote a higher Trp-to-LCNAA ratio and have a greater serotonergic effect (36). Moreover, it has been reported that the Trp-to-LCNAA ratio peaks between 2 and 4 h after the ingestion of an HC meal (36), which likely accounts for shorter SOL after the consumption of an HC or high-GI meal 4 h compared with 1 h before bedtime (23).…”
Section: Dietary Patterns and Sleep Qualitysupporting
confidence: 55%
See 3 more Smart Citations
“…In support of this, a correlation between plasma glucose and insulin, and peak Trp:LCNAA has been reported (36). Therefore, an HC diet, especially one with a high GI, would promote a higher Trp-to-LCNAA ratio and have a greater serotonergic effect (36). Moreover, it has been reported that the Trp-to-LCNAA ratio peaks between 2 and 4 h after the ingestion of an HC meal (36), which likely accounts for shorter SOL after the consumption of an HC or high-GI meal 4 h compared with 1 h before bedtime (23).…”
Section: Dietary Patterns and Sleep Qualitysupporting
confidence: 55%
“…With the consumption of an HC diet, the resulting higher postprandial insulin enhances the Trp-to-LCNAA ratio by facilitating uptake of LCNAA by muscle, further promoting Trp entry into the brain and enabling serotonin production (23). In support of this, a correlation between plasma glucose and insulin, and peak Trp:LCNAA has been reported (36). Therefore, an HC diet, especially one with a high GI, would promote a higher Trp-to-LCNAA ratio and have a greater serotonergic effect (36).…”
Section: Dietary Patterns and Sleep Qualitymentioning
confidence: 87%
See 2 more Smart Citations
“…On the other hand, TRP is scarce in most protein sources, and is readily metabolised on passage through the liver; thus, the plasma ratio of TRP to competing amino acids falls after a proteinrich meal (Schweiger et al 1986b;Yokogoshi & Wurtman, 1986;Christensen, 1993). Indeed, the protein-induced reduction in plasma TRP ratio often seems to be more marked than any carbohydrate-induced rise (Lieberman et al 1986;Lyons & Truswell, 1988;Wolever et al 1988;Christensen & Redig, 1993). Such effects also depend on the interval since, and nutrient content of, the last meal (Fernstrom & Fernstrom, 1995).…”
Section: Protein V Carbohydratementioning
confidence: 99%